KCl FERTILIZER AND GOAT Urine EFFECT ON PRODUCTION OF JAPANESE CUCUMBER PLANTS (Cucumis sativus var. Japonese) - Lubis, Efrida; Novita, Aisar; Bahri, Khoirul; Gandaseca, Seca (International Journal of Biosciences and Biotechnology; Vol 10 No 1 (2022): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2022)
The research was carried out from June to completion, at the Deli Tobacco Research Institute (BPTD) Sampali PTPN II. This study aims to determine the effect of KCl fertilizer and goat urine on the growth and yield of Japanese cucumbers. This study used a factorial randomized block design (RAK) with 2 factors. The first factor is KCl with 4 levels, namely S0 (Control), S1 (10 g/plant), S2 (20 g/plant), S3 (30 g/plant) the second factor is Goat Urine with 4 levels, namely K0 (Control), K1 (200 ml/plant), K2 (400 ml/plant) and K3 (600 ml/plant). Parameters measured were vine length, leaf number, leaf area, number of fruit per plant, fruit length, number of fruit per plot, fruit weight per plant and fruit weight per plot. The results showed that KCl fertilizer had an effect on the number of fruits per plant and the number of fruits per plot but the administration of goat urine had no effect on all parameters. The interaction of KCl fertilizer and goat urine did not affect all parameters.